Post-translational regulation of TGF-β receptor and Smad signaling - Xu, Pinglong (FEBS Lett, 2012)
TGF-β family signaling through Smads is conceptually a simple and linear signaling pathway, driven by sequential phosphorylation, with type II receptors activating type I receptors, which in turn activate R-Smads. Nevertheless, TGF-β family proteins induce highly complex programs of gene expression responses that are extensively regulated, and depend on the physiological context of the cells. Regulation of TGF-β signaling occurs at multiple levels, including TGF-β activation, formation, activation and destruction of functional TGF-β receptor complexes, activation and degradation of Smads, and formation of Smad transcription complexes at regulatory gene sequences that cooperate with a diverse set of DNA binding transcription factors and coregulators. Here we discuss recent insights into the roles of post-translational modifications and molecular interaction networks in the functions of receptors and Smads in TGF-β signal responses. These layers of regulation demonstrate how a simple signaling system can be coopted to exert exquisitely regulated, complex responses.